2016
DOI: 10.1016/j.pscychresns.2016.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Altered neurotransmitter metabolism in adolescents with high-functioning autism

Abstract: Previous studies have suggested that alterations in excitatory/inhibitory neurotransmitters might play a crucial role in autism spectrum disorder (ASD). Proton magnetic resonance spectroscopy (1H-MRS) can provide valuable information about abnormal brain metabolism and neurotransmitter concentrations. However, few 1H-MRS studies have been published on the imbalance of the two most abundant neurotransmitters in ASD: glutamate (Glu) and gamma-aminobutyric acid (GABA). Moreover, to our knowledge none of these pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 49 publications
2
54
0
Order By: Relevance
“…Fifteen participants with ASD were recruited from the special secondary education school, de Berkenschutse (located in Heeze, the Netherlands), as detailed previously. 22 All high-functioning adolescents with ASD fulfilled established diagnostic criteria according to the DSM-IV, as well as the autism algorithm cut-offs on the Autism Diagnostic Observation Schedule (ADOS). 26 The HC group consisted of 18 normally developing adolescents who were recruited through advertisements in newspapers and most were living in other parts of the country.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen participants with ASD were recruited from the special secondary education school, de Berkenschutse (located in Heeze, the Netherlands), as detailed previously. 22 All high-functioning adolescents with ASD fulfilled established diagnostic criteria according to the DSM-IV, as well as the autism algorithm cut-offs on the Autism Diagnostic Observation Schedule (ADOS). 26 The HC group consisted of 18 normally developing adolescents who were recruited through advertisements in newspapers and most were living in other parts of the country.…”
Section: Participantsmentioning
confidence: 99%
“…By assessing these two groups, the potential influence of intellectual impairment rather than ASD is removed. 22 Furthermore, adolescents with high-functioning autism are more prone to psychosocial stress than their low-functioning counterparts, as they are more aware of opinions and evaluations of peers. 23,24 It has been suggested that during adolescence, a complex frontoparietal network of brain regions is involved in WM processes (for review, see Barendse et al 17 ).…”
mentioning
confidence: 99%
“…MRS measurements of GABA have been associated with individual differences in hemodynamic and electrophysiological signals (Donahue et al, 2010; Hu et al, 2013; Kapogiannis et al, 2013; Muthukumaraswamy et al, 2009) and a number of measures of cognition (Fujihara et al, 2015; Shibata et al, 2017; Yoon et al, 2016) and behavior (Boy et al, 2011; Greenhouse et al, 2017; Puts et al, 2011; Silveri et al, 2013). Differential levels of GABA have been observed in a number of neuropsychiatric disorders, such as schizophrenia (Kegeles et al, 2012; Öngür et al, 2010; Rowland et al, 2016; Yoon et al, 2010) and depression (Bhagwagar et al, 2008; Hasler et al, 2007; Price et al, 2009), neurodevelopmental disorders such as autism spectrum disorder (Drenthen et al, 2016; Gaetz et al, 2014; Puts et al, 2016) and attention deficit hyperactivity disorder (Bollmann et al, 2015; Edden et al, 2012a), and neurological diseases, such as Parkinson’s disease (Emir et al, 2012), amyotrophic lateral sclerosis (Foerster et al, 2012; Foerster et al, 2013) and diabetic neuropathy (Petrou et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…While this review does not pertain to cognition, an understanding of the relationship between GABA and cognition motivates our initial step towards understanding the relationship between GABA and age. Alterations of GABA levels are seen in neurodevelopmental disorders such as ADHD (Bollmann et al, 2015;Edden et al, 2012), Autism Spectrum Disorder (Cochran et al, 2015;Drenthen et al, 2016;Gaetz et al, 2014;Puts et al, 2017), and Tourette syndrome (Puts et al, 2015), as well as in other neurological and psychiatric disorders including schizophrenia (Rowland et al, 2016;Shaw et al, 2020), depression (Sanacora et al, 1999) and neurofibromatosis (Violante et al, 2013). These associations are reviewed by Puts and Edden (2012) and by Schür et al (2016).…”
mentioning
confidence: 99%